Facile synthesis of Fe nanospheres anchored aminoclay and its catalytic reduction of hazardous pollutants and oxidation activity. Issue 11 (31st August 2021) - Ranchani, A. Amala Jeya; Parthasarathy, V.; Mahalakshmi, S.; Anbarasan, R.
Abstract: A novel Fe anchored aminoclay was prepared and characterized. The prepared novel Fe-AC catalyst was tested toward both the reduction and oxidation reactions. The catalytic reduction was achieved toward the removal of the three pollutants such as fluorescein dye, nitrophenol (NP) and Cr(VI) using Fe-AC system. The catalytic reduction study was quantified by UV-visible spectroscopy and the kapp value was determined to assess the reduction efficiency of the prepared catalyst on the removal of hazardous pollutants. The Fe-AC catalyst yielded higher kapp values for the reduction of individual pollutant than the binary and tri-pollutant systems. 91% of Cr(VI) and NP was found to be reduced in 12 mins in their binary pollutants mixture. The Schiff base formation was also carried out to examine the oxidation activity of Fe-AC catalyst and the same was confirmed through 1 H-NMR spectra. Graphical abstract: UF0001 UV-visible spectra of NiP + fluorescein dye + Cr(VI) (a) and kapp plot of FR dye system (b) and Cr(VI)+NP complex system (c) .